Imaging-guided precision medicine in non-resectable gastro-entero-pancreatic neuroendocrine tumors: A step-by-step approach. Issue 122 (January 2020) - Rozenblum, Laura; Mokrane, Fatima-Zohra; Yeh, Randy; Sinigaglia, Mathieu; Besson, Florent L.; Seban, Romain-David; Zadro, Charline; Dierickx, Lawrence; Chougnet, Cecile N; Partouche, Ephraim; Revel-Mouroz, Paul; Zhao, Binsheng; et al.
Highlights: Medical imaging is pivotal for risk stratification and treatment planning. Imaging assesses non-invasively tumor spatial and temporal heterogeneity. The diagnostic accuracy of medical imaging varies with tumor type and metastatic site. There are several interventional approaches in non-resectable patients. Response assessments should be tailored to the type of systemic treatments. Abstract: The majority of gastroenteropancreatic (GEP) neuroendocrine tumors (NETs) are diagnosed at a non-resectable stage due to non-specific clinical syndromes, late manifestations from mass effects, or incidental detection of a clinically silent disease. Management strategies include curative or cytoreduction surgery, imaging-guided intervention, chemotherapy, immunotherapy, and radionuclide therapies. In this step-by-step review, we provide a structured approach for standardized reading and reporting of medical imaging studies covering content and terminology. This review explains which imaging studies should be used for different NETs and what should be reported when interpreting these studies. This standardized data collection guide should enable precision medicine for the management of patients with GEP-NETs of neuroectodermal origin: gastrointestinal-NETs (giNETs) and pancreatic NETs (pNETs). To improve outcomes from GEP-NETs, it contains a comprehensive evaluation of imaging aids for determining surgical non-resectability, and serves as a surrogate measure for tumor differentiation and proliferation, assessing the spatial and temporal heterogeneity of the tumor sites with prognostic and therapeutic implications.